IrO2-Decorated Titania Nanotubes as Oxygen Evolution Anodes - Aikaterini Touni; Effrosyni Mitrousi; Patricia Carvalho; Maria Nikopoulou; Eleni Pavlidou; Dimitra A. Lambropoulou; Sotiris Sotiropoulos (Molecules)
In this work, we have used both plain titania nanotubes, TNTs, and their reduced black analogues, bTNTs, that bear metallic conductivity (prepared by solid state reaction of TNTs with CaH2 at 500 °C for 2 h), as catalyst supports for the oxygen evolution reaction (OER). Ir was subsequently been deposited on them by the galvanic replacement of electrodeposited Ni by Ir(IV) chloro-complexes; this was followed by Ir electrochemical anodization to IrO2. By carrying out the preparation of the TNTs in either two or one anodization steps, we were able to produce close-packed or open-structure nanotubes, respectively. In the former case, larger than 100 nm Ir aggregates were finally formed on the top face of the nanotubes (leading to partial or full surface coverage); in the latter case, Ir nanoparticles smaller than 100 nm were obtained, with some of them located inside the pores of the nanotubes, which retained a porous surface structure. The electrocatalytic activity of IrO2 supported on open-structure bTNTs towards OER is superior to that supported on close-packed bTNTs and TNTs, and its performance is comparable or better than that of similar electrodes reported in the literature (overpotential of η = 240 mV at 10 mA cm−2; current density of 70 mA cm−2 and mass specific current density of 258 mA mgIr−1 at η = 300 mV). Furthermore, these electrodes demonstrated good medium-term stability, maintaining stable performance for 72 h at 10 mA cm−2 in acid.